AN EXPERIMENTAL STUDY TO CHILDHOOD OBESITY INFORMATION EDUCATION AND COMMUNICATION (IEC) AMONG PARENTS OF OBESE CHILDREN - , Edna Sweenie J; Dr. Anu V. Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Initial data was collected on demographic and clinical variables and then pretest was given on knowledge, attitude and compliance towards weight reducing measures on childhood obesity for both the groups through a structured questionnaire before implementing IEC. Subjects who fulfilled the inclusion criteria, during the period of study were considered as sample. They were randomly assigned to study or control group by using lottery method. there were 100 samples in the study group and 100 samples in control group. Researchers found that students who participated in school-based treatments had a significant decrease in their body mass index. Involving parents in health promotion programs at school encourages students to keep up their healthy habits, which helps significantly in the fight against childhood obesity. The children really take to the group program and excel in it. Children's inactive time must be limited, and they must be encouraged to participate in physical activity.